Medication adherence in hypertension. Issue 4 (April 2020) - Poulter, Neil R.; Borghi, Claudio; Parati, Gianfranco; Pathak, Atul; Toli, Diana; Williams, Bryan; Schmieder, Roland E.
Abstract : N/A: Suboptimal adherence to antihypertensive medication is a major contributor to poor blood pressure control. Several methods, direct or indirect, are available for measuring adherence, including the recently developed biochemical screening, although there is no gold-standard method routinely used in clinical practice to accurately assess the different facets of adherence. Adherence to treatment is a complex phenomenon and several of the barriers to adherence will need to be addressed at the healthcare system level; however, when looking at adherence from a more practical side and from the practitioner's perspective, the patient–practitioner relationship is a key element both in detecting adherence and in attempting to choose interventions tailored to the patient's profile. The use of single-pill combinations enabling simplification of treatment regimen, the implementation of a collaborative team-based approach and the development of electronic health tools also hold promise for improving adherence, and thus impacting cardiovascular outcomes and healthcare costs.